2023
DOI: 10.1051/e3sconf/202339101011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Of Machining Parameters of CNC Milling Operation for Material Removal Rate and Surface Roughness on En-24 Steel Using Taguchi Method

Abstract: The significance of quality and productivity in the manufacturing industry cannot be overstated, as they directly impact profitability. To remain competitive and keep pace with advancements in technology, manufacturing industries must continuously improve their processes to enhance the quality and productivity of their products. One technology that has contributed to such improvements is CNC milling machines, which have been used in this study. For this study, the high-strength, ductile, and wear-resistant ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Surface roughness is reduced when coolant is used. Satyanarayana et al (2023) aimed to analyze the optimal parameters for fly (face) milling of components composed of AISI 1045 steel in terms of surface finish and energy consumption. The study found that the most effective fly milling performance for fast manufacturing (case 1) is achieved with a feed per tooth of fz = 0.25 mm/tooth, cutting speed of vc = 392.6 m/min, and machined length of l = 5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness is reduced when coolant is used. Satyanarayana et al (2023) aimed to analyze the optimal parameters for fly (face) milling of components composed of AISI 1045 steel in terms of surface finish and energy consumption. The study found that the most effective fly milling performance for fast manufacturing (case 1) is achieved with a feed per tooth of fz = 0.25 mm/tooth, cutting speed of vc = 392.6 m/min, and machined length of l = 5 mm.…”
Section: Introductionmentioning
confidence: 99%